SURAU SEBAGAI BASIS ISLAMISASI KULTURAL MASYARAKAT MINANGKABAU - Welhendri Azwar (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2015)
Observing various dakwah activity today, rather feels that the essence of dakwah began to lose value. Dakwah is no longer able to give directions over the life of the Islamic community. Moreover, if the dakwah activity is packed with business media, especially television, this may seem to add “syi'ar”of Islam, but actually she's dragged to the artificiality meaning of divine messages. Dakwah activity tends to significantly spectacle, versus guidance. When studied in the early development of Islamic Dakwah, it’s succeeded in giving the color of people's lives. Dakwah instead act to strengthen the local culture with a strong Islamic characterize. Islam in Minangkabau characterize it has become increasingly apparent. The combination of local and Islamic culture are felt in many Minang people's lives. One of the most influential cultural symbol in Minangkabau is the message of Islam, "surau". This paper seeks to provide an answer to how the concept of “surau” at  the development of Islam in Minangkabau, and how the dakwah strategy of the surau, as well as how social functioning surau in the Minangkabau society. The study used a descriptive - phenomenological approach, a method that emphasizes the meaning to the understanding of society. In epistemology, the study is based on empirical generalizations and determination concepts. The results of this study indicate that the meaning of the surau had been developed through a process of social Islamization. Furthermore, surau important role in the development and spread of Islam in Minangkabau, as a center of dakwah and educational activities , as well as the center of social activities. Surau role in maintaining its existence as a social institution in fostering the values of divinity and humanity in the social relations. At the same time, surau has a socially established itself as one of the important parts of the socio-cultural system of the Minangkabau society. So conceptually, surau style education can serve as a role mode propagation methods and strategies based on the knowledge of local culture